Performance Analyses of Combined Cycle Power Plants - KARAALİ , Rabi (International Journal of Computational and Experimental Science and Engineering, 2023)
In this article, different compressor pressure and different excess air rates for a gas turbine based combine cycle power plant with steam Rankine cycle as bottoming cycle were analyzed by using 1. and 2. laws of thermodynamics and exergy analyses methods to obtain the best performances of the cycle. Exergy efficiency of the cycle, net powers of the gas and steam turbines and the overall cycle, exergy loss of the components, the efficiencies of the components are obtained, compared and discussed. It was found that, increasing the compressor pressure increases exergy efficiency of cycle, gas turbine and total plant power, and the combustion chamber, the HRSG and the compressor efficiencies. However, increasing compression rates decreases steam turbine power, combustion chamber, steam turbine, and HRSG exergy losses and the gas turbine efficiency. Also, it is found that, increases in excess air ratios gives an optimum or a maximum exergy efficiency, at 2.5 excess air rate of the cycle.